A temperature-based model of biomass accumulation in humid forests of the world - Larjavaara, Markku; Chen, Xia; Luo, Mingyu (Frontiers in Forests and Global Change, 2024)
Forests benefit humans in numerous ways. Many of these benefits are greater from forests with large trees and high biomass (i.e., above-ground biomass) than from young forests with small trees. Understanding how the biomass accumulation rate depends on climate is therefore important. According to a classic theory, the biomass accumulation rate first increases until canopy closure, as leaf area and gross primary productivity increase, and decreases thereafter because leaf area cannot increase further and maintaining larger biomass is energetically costlier as living tissue increases even though its proportion of all biomass decreases. We based our modeling on this classic theory and defined relative productivity, pr indicating productivity, and relative maintenance cost, cr, signaling the expense of sustaining a unit of biomass in humid climates of the world. The biomass accumulation rate of low biomass forests is determined by pr − cr and maximal biomass by pr/cr. We then compiled a global data set from the literature, with 3,177 records to fit a parameter for the efficiency of converting surplus carbon into accumulated biomass and another parameter determining biomass at canopy closure. Based on the parameterized models, a constant temperature of 22.3°C leads to the most rapid biomass accumulation in low biomass forests, whereas 16.4°C results in greatest maximal biomass. Our parameterized model can be applied to both climate change adaptation and mitigation by optimizing land use.